Respuesta :

Answer:

veiw the screenshot

Step-by-step explanation:


Ver imagen arrrstybunnny

Answer:

The required graph is shown below:

Step-by-step explanation:

Consider the provided equation.

[tex]y=3(0.5)^x[/tex]

The graph of the function is a exponential graph.

Substitute x=-2 in [tex]y=3(0.5)^x[/tex]

[tex]y=3(0.5)^{-2}[/tex]

[tex]y=\frac{3}{0.25}[/tex]

[tex]y=12[/tex]

Substitute x=-1 in [tex]y=3(0.5)^x[/tex]

[tex]y=3(0.5)^{-1}[/tex]

[tex]y=\frac{3}{0.5}[/tex]

[tex]y=6[/tex]

Substitute x=0 in [tex]y=3(0.5)^x[/tex]

[tex]y=3(0.5)^0[/tex]

[tex]y=3[/tex]

Substitute x=1 in [tex]y=3(0.5)^x[/tex]

[tex]y=3(0.5)^1[/tex]

[tex]y=1.5[/tex]

Substitute x=2 in [tex]y=3(0.5)^x[/tex]

[tex]y=3(0.5)^2[/tex]

[tex]y=0.75[/tex]

Now draw the table as shown.

x   -2   -1    0   1        2

y   12   6    3   1.5  0.75

With the help of the table draw the graph.

The required graph is shown below:

Ver imagen FelisFelis